Digital Signal Processing Solutions for Motor Control Using the TMS320F240 DSP-Controller - Jimirafizi, Jamil; Ismail, Daut; Tunku Nizar; Shuib, Taib (Kolej Universiti Kejuruteraan Utara Malaysia, 2008)
Link to publisher's homepage at http://jere.unimap.edu.my